2003
DOI: 10.4049/jimmunol.171.1.438
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Infection of Human Microvascular Endothelial Cells by Coxsackie B Viruses Induces Increased Expression of Adhesion Molecules

Abstract: Numerous studies indicate that enteroviruses, such as the Coxsackievirus (CV) group, are linked to autoimmune diseases. Virus tropism and tissue access are modulated by vascular endothelial cells (ECs), mainly at the level of the microvasculature. Data on the permissiveness of ECs to CV are, however, scanty and derived from studies on large vessel ECs. To examine the susceptibility of microvascular ECs to infection of group B CV (CVB), human dermal microvascular ECs (HMEC-1) were infected with three CVB strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 47 publications
5
45
0
2
Order By: Relevance
“…Phenotypic characterisation and detection of endothelial cell surface molecules From the earliest passages for which sufficient cells were available for study, endothelial phenotype was assessed by flow cytometric analysis of the cell surface phenotype, staining for basal expression of endothelial markers and adhesion molecules, or of permeabilised cells for intracellular von Willebrand factor (vWF) staining, as described [32]. The following antibodies were used: anti-human monoclonal antibody against CD105-R-phycoerythrin (undiluted; Serotec, Oxford, UK), CD146-fluorescein isothiocyanate (FITC) (clone P1H12, final dilution 1:100) (Chemicon, Temecula, CA, USA), E-selectin (CD62E, final dilution 1:100), intercellular adhesion molecule-1 (ICAM-1) (CD54, 1:10), CD106 (vascular cell adhesion molecule-1 [VCAM-1], 1:20) (all from Serotec), rabbit anti-human vWF antiserum (1:200) (Sigma) and R-phycoerythrin-conjugated F (ab′) 2 fragment of goat anti-mouse immunoglobulins or R-phycoerythrin-conjugated anti-rabbit immunoglobulins (Dako, Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Phenotypic characterisation and detection of endothelial cell surface molecules From the earliest passages for which sufficient cells were available for study, endothelial phenotype was assessed by flow cytometric analysis of the cell surface phenotype, staining for basal expression of endothelial markers and adhesion molecules, or of permeabilised cells for intracellular von Willebrand factor (vWF) staining, as described [32]. The following antibodies were used: anti-human monoclonal antibody against CD105-R-phycoerythrin (undiluted; Serotec, Oxford, UK), CD146-fluorescein isothiocyanate (FITC) (clone P1H12, final dilution 1:100) (Chemicon, Temecula, CA, USA), E-selectin (CD62E, final dilution 1:100), intercellular adhesion molecule-1 (ICAM-1) (CD54, 1:10), CD106 (vascular cell adhesion molecule-1 [VCAM-1], 1:20) (all from Serotec), rabbit anti-human vWF antiserum (1:200) (Sigma) and R-phycoerythrin-conjugated F (ab′) 2 fragment of goat anti-mouse immunoglobulins or R-phycoerythrin-conjugated anti-rabbit immunoglobulins (Dako, Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Amongst these, vascular endothelial cells have an established role as mediators of tissue tropism and access for virus, influencing organ and tissue specific susceptibility to viral infection. Therefore, they can modulate the pathological expression of virus-induced diseases (Friedman et al, 1981;Huber et al, 1990;Conaldi et al, 1997;Zanone et al, 2003). For instance, in murine studies on CVB infectivity of different organs, CVB3 isolates from the heart showed greater infectivity and replication in heart endothelial cells than endothelial cells derived from liver or lung (Huber et al, 1990), thus confirming the essential role of host factors in developing specific diseases.…”
Section: Coxsackievirus Infection and Endothelial Cellsmentioning
confidence: 85%
“…However, physiological and pathological events take place mainly at the level of the microvasculature. Using a dermal microvascular endothelial cell line, we have provided evidence that small vessel endothelial cells can harbour a persistent CVB viral infection (Zanone et al, 2003). All 3 CVB tested productively infected microvascular endothelial cells for up to 3 months without obvious cytolysis.…”
Section: Coxsackievirus Infection and Endothelial Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…O tropismo desses vírus pela musculatura também foi demonstrado pelo isolamento do vírus do miocárdio de pacientes com miocardite aguda (11) . Nas infecções pelo vírus Coxsackie há aumento significativo de moléculas de adesão celulares ICAM-1 e VCAM-1 no endotélio capilar e venoso e aumento na produção de citocinas proinflamatórias, como IL-6, IL-8 e TNF-α, fatores que modificam a resposta imune do hospedeiro (12) . O quadro crônico de miosite, como a miocardite crônica induzida pelo Coxsackie, é explicado por mecanismos de imunidade cruzada relacionados com homologias entre os peptídeos virais e os próprios da membrana celular, assim como a inclusão de antígenos virais no sarcolema durante a regeneração das fibras musculares (13) .…”
Section: Discussionunclassified